Comparison and its role in creating artistic images in the poems of Ahmad Mukhtar Beg Jaf - گەردى, سەردار ئەحمەد (Sulaimani Journal for Humanities, 2001)
The simile and its role in Formation of poetic images in Ahmad Mukhtar Jafs poetries. The simile is considred as one of demonstrative arts and its essentilly divided in to; The direet simile 2- The indirect simile. The direct simile: in this kind the similartiy and similartiy with are quite clear. The indirect simile from which the similarity and the similarity and the similarity with disapper. Also the simile is divided where as contains the rules or not. Since the formation the poetic image the simile has become the most important side in poetic drawings. Ahmad muktar jaf ,tried hard using simile for fathest extent especially. The used eloquent arts by him settled thole arts and versed in his thought. His artistic images arecreative and fussed his gift in it.